Management of Community Fund by Good Governance: A Case Study of Community Fund of Banchoraka, Nafai Sub-district, Muang District, Chaiyaphu - Sunthorn , Panyapong; Chaisri, Anchali; Duangmala, Tassanaiwan; Khumchaibhum, Vatunyu; Prungchaibhum, Vimolsil (Academic MCU Buriram Journal, 2019)
This research has a purpose 1) to study the fund management as corporate governance, 2) to study the difficulties in the village operations department. A sample group is a member of the Provident 83 people. The tools for data collection and statistics are average percentage and standard deviation values. The results of the research showed that the community fund management has been mainly the Community Fund Committee in its operations based on the good governance. The overall image is very high. It comprises of the principles of the law, principles of transparency, participation principle and principles of value. The problems and barriers to the operations of the village fund found the borrowing from the community fund approval of the Board of Directors' loan, receiving and returning loans is an important issue in the fund management, respectively. The study in this area can give people the ability to learn the management in a community that has good work to learn the management of the community fund and the key is to remove the process. New ideas continue to apply to the community for the next future.